Limitations of MALDI-TOF MS in identifying anaerobic bacteremia: challenges in polymicrobial infections and the role of whole-genome sequencing - Takuya Hosoda; Masahiro Suzuki; Takahiro Matsuno; Kenjiro Matsui; Koji Ohyama; Yohei Doi (Microbiology Spectrum)
ABSTRACT With the widespread use of matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS), the number of identifiable bacterial species has increased. However, anaerobic bacteremia remains challenging to accurately diagnose due to the diverse range of anaerobic bacteria and the frequent occurrence of polymicrobial infections. Consequently, MALDI-TOF MS often fails to achieve accurate species-level identification in such cases. To address this limitation, we evaluated whole-genome sequencing (WGS) as an alternative method for identifying anaerobic bacteria in blood cultures. Over a 4-year period (April 2020 to March 2024), 69 cases of anaerobic bacteremia were identified, involving 85 bacterial strains. WGS successfully identified 73 strains (89%) at the species level. MALDI-TOF MS accurately identified 43 strains (59%) at the species level and 6 strains (8.2%) at the genus level. Among the 24 discordant strains, 9 species were not included in the database, and 6 species had limited prior reports of bloodstream infections. Additionally, 21 of the 69 cases (30%) were polymicrobial, and WGS revealed 9 cases (13%) in which multiple species had not been identified by MALDI-TOF MS. These results highlight the limitations of MALDI-TOF MS in anaerobic bacterial identification, particularly in polymicrobial infections, and suggest that alternative molecular approaches are necessary to improve diagnostic accuracy.IMPORTANCEAccurate identification of anaerobic bacteria remains a significant challenge despite the widespread use of matrix-assisted laser desorption ionization time-of-flight mass spectrometry. While this technology has improved the detection of many bacterial species, some anaerobes remain unidentified due to their absence from reference databases and the difficulties associated with their isolation, particularly in polymicrobial infections. Whole-genome sequencing (WGS) has revealed previously unreported anaerobes and identified polymicrobial infections that were initially misclassified as monomicrobial. Our findings underscore the importance of implementing molecular approaches such as WGS- or PCR-based methods in clinical diagnostics to improve the detection of anaerobic pathogens.